Perbedaan Rasio Trombosit Limfosit pada Kanker Serviks Tipe Karsinoma Sel Skuamosa dan Adenokarsinoma - Bella Aprilia Damayanti; Hariadi Yuseran; F.X. Hendriyono (Homeostasis, 2022)
Abstract: Cervical cancer is an abnormal cell growth that leads to malignancy in the cervix. Cervical cancer has several cell types including squamous cell carcinoma (SCC) and adenocarcinoma type. The progression of cervical cancer is influenced by many factors, including platelets and the immune system, namely lymphocytes. The ratio of platelets to lymphocytes affects the progression and prognostic markers of cervical cancer. This study aims to determine whether there are differences in RTL in cervical cancer type SCC and adenocarcinoma. The results showed that 58 subjects with cervical cancer, 29 subjects with SCC type and 29 subjects with adenocarcinoma type. The mean RTL value for cervical cancer with SCC type was 196.4 and standard deviation was 105.3 and the mean RTL value for adenocarcinoma type was 163.9 and standard deviation was 59.0. The conclusion of this study is that there is a significant difference in RTL in cervical cancer type SCC and adenocarcinoma with p = 0.000. Keywords: cervical cancer, SCC, adenocarcinoma, RTL Abstrak: Kanker serviks merupakan pertumbuhan sel abnormal yang mengarah pada keganasan di leher rahim. Kanker serviks memiliki beberapa tipe sel diantaranya ada tipe karsinoma sel skuamosa (KSS) dan tipe adenokarsinoma. Progresivitas kanker serviks dipengaruhi banyak faktor, diantaranya trombosit dan sistem imun yaitu limfosit. Rasio trombosit limfosit mempengaruhi progresivitas dan penanda prognostik pada kanker serviks. Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan RTL pada kanker serviks tipe KSS dan adenokarsinoma. Hasil penelitian didapatkan 58 subjek kanker serviks, 29 subjek tipe KSS dan 29 subjek tipe adenokarsinoma. Hasil rerata nilai RTL pada kanker serviks tipe KSS adalah 196,4 dan simpang baku105,3 dan rerata nilai RTL pada tipe adenokarsinoma adalah 163,9 dan simpang baku 59,0. Kesimpulan penelitian ini adalah terdapat perbedaan bermakna RTL pada kanker serviks tipe KSS dan adenokarsinoma dengan p=0,000. Kata – kata kunci : kanker serviks, KSS, adenokarsinoma, RTL